Penggunaan Pembelajaran Kooperatif Tipe Take and Give untuk Meningkatkan Hasil Belajar Materi Menentukan Nilai Limit Fungsi Aljabar pada Peserta Didik Kelas XII Tata Boga 4 SMK Negeri 2 Godean - Harwidi, Dini (Nusantara: Jurnal Pendidikan Indonesia, 2021)
This study aims to improve learning outcomes to determine the limit value of algebraic functions in students of class XII Tata Catering 4 SMK Negeri 2 Godean semester 1 of the 2019/2020 academic year through cooperative learning Type Take and Give. And describe the steps of implementing the Take and Give the type of cooperative learning to achieve completeness of learning outcomes to determine the limit value of classical algebraic functions in class XII Catering 4 students of SMK Negeri 2 Godean semester 1 of the 2019/2020 academic year. Research procedures through planning, implementation, observation and monitoring, and reflection. Data collection techniques through observation, field notes, and written tests. Types of instruments and how to use them with an observation guide. The data analysis technique used qualitative analysis. The results showed that in the implementation of learning to determine the value of the limit of algebraic functions through cooperative learning Type Take and Give in Cycle I, students who achieved KKM 58.06%. The average test result score was 67.50. In the second cycle students who reach KKM 87.10%. The average test result score was 75.81.